2018
DOI: 10.1038/s41467-018-05772-7
|View full text |Cite
|
Sign up to set email alerts
|

Memory B cells are reactivated in subcapsular proliferative foci of lymph nodes

Abstract: Vaccine-induced immunity depends on the generation of memory B cells (MBC). However, where and how MBCs are reactivated to make neutralising antibodies remain unknown. Here we show that MBCs are prepositioned in a subcapsular niche in lymph nodes where, upon reactivation by antigen, they rapidly proliferate and differentiate into antibody-secreting plasma cells in the subcapsular proliferative foci (SPF). This novel structure is enriched for signals provided by T follicular helper cells and antigen-presenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
84
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 77 publications
3
84
0
Order By: Relevance
“…CCL20 has been linked to Innate Lymphoid Cell (ILC) trafficking across the SCS [14] and may affect the cross-talk between CCR6 positive DCs and LECs in antigen presentation [39]. CCL20 could also influence B-cell homeostasis, as memory B-cells precursors are distinguished by high CCR6 expression in lymphoid organs of both mouse and man [40] and are closely associated to the SCS [41]. CXCL1 may instead contribute to neutrophil migration and recruitment [42].…”
Section: Resultsmentioning
confidence: 99%
“…CCL20 has been linked to Innate Lymphoid Cell (ILC) trafficking across the SCS [14] and may affect the cross-talk between CCR6 positive DCs and LECs in antigen presentation [39]. CCL20 could also influence B-cell homeostasis, as memory B-cells precursors are distinguished by high CCR6 expression in lymphoid organs of both mouse and man [40] and are closely associated to the SCS [41]. CXCL1 may instead contribute to neutrophil migration and recruitment [42].…”
Section: Resultsmentioning
confidence: 99%
“…122 255 Although memory B cells have been reported to be positioned within lymphoid tissues at marginal zones, perifollicular zones, and some follicles after the resolution of response, 255,259,260 two studies have reported a predominant FM location for Ki67memory B cells in spleens and LNs. 249,250 Although the above studies support the idea that memory B cells primarily exit via follicle adjacent sinuses, it is worth noting that CCR6hi memory B cells are also responsive to CXCL12. 255…”
Section: Follicular Mantlementioning
confidence: 78%
“…22,122 After the resolution of a primary response, both memory B cells and memory Tfh cells can be found within FMs, a positioning that is influenced by their EBI2 expression. 122,249,250 Theoretically, this compartment could influence the differentiative state of antigen-specific B cells that are leaving the GC via this route. As cells within this arena are less likely to be in active cell cycle, this environment may be more conducive to gaining a quiescent state, sheltered from the cellular interactions that promote a centroblast program and their self-renewal.…”
Section: Follicular Mantlementioning
confidence: 99%
See 2 more Smart Citations